2015
DOI: 10.1007/s13580-015-0060-y
|View full text |Cite
|
Sign up to set email alerts
|

Compositions of fatty acids and phytosterols of plant-based oils and their associations with anti-oxidative capacity: Application of principal component analysis

Abstract: Complete fatty acid profile and major phytosterols of nearly all commercially available vegetable oils, obtained from local grocery stores in South Korea, were analyzed (n = 15). Subsequently, the contribution of specific oil components to antioxidative effects, measured using conventional 2,2-diphenyl-1-picrylhydrazyl (DPPH) and 2',7'-dichlorofluorescindiacetate (DCF-DA) assays, was assessed via principal component analysis (PCA). The rat pheochromocytoma cell line was used for the DCF-DA analysis. One of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 21 publications
0
0
0
Order By: Relevance
“…Despite this error, the sample was still identified as adulterated, indicating that the classifier was able to differentiate between sesame and sunflower oil adulterations even at low concentrations in quince seed oil samples. Kim et al [27] analyzed the fatty acid composition of various vegetable oils, including sesame, quince seed, and sunflower oils. The analysis revealed that sesame oil and quince seed oil had similar fatty acid profiles, with both oils containing high amounts of oleic acid and linoleic acid.…”
Section: Classification Optimization and Accuracymentioning
confidence: 99%
“…Despite this error, the sample was still identified as adulterated, indicating that the classifier was able to differentiate between sesame and sunflower oil adulterations even at low concentrations in quince seed oil samples. Kim et al [27] analyzed the fatty acid composition of various vegetable oils, including sesame, quince seed, and sunflower oils. The analysis revealed that sesame oil and quince seed oil had similar fatty acid profiles, with both oils containing high amounts of oleic acid and linoleic acid.…”
Section: Classification Optimization and Accuracymentioning
confidence: 99%